(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
It is known that in recent years consistent reforms have been implemented in our country on effective use of water resources, improvement of their management system, modernization and development of water management facilities. In this article, the changes in the water management system, its problems and the results of reforms carried out in the field are presented and conclusions are drawn.